2019
DOI: 10.1590/s1677-5538.ibju.2019.0097
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the effect of adherent perinephric fat on outcomes of robotic assisted partial nephrectomy following elimination of the learning curve

Abstract: Purpose: To prospectively evaluate the association of adherent perinephric fat (APF) on perioperative outcomes of robotic-assisted partial nephrectomy (RAPN) following elimination of the surgical learning curve. Materials and Methods: 305 consecutive RAPNs performed by a single experienced surgeon were analyzed. The first 100 RAPNs were considered the learning curve and therefore excluded. APF was defined as the necessity of subcapsular renal dissection to mobilize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
2
7
1
Order By: Relevance
“…We did not observe a significant difference in warm ischemia time in both subgroups, and there was no difference in positive surgical margins or in overall complications. This is in line with Shumate et al’s [26] recently published results of 205 patients undergoing RAPN. In that study, the presence of APF was not associated with warm ischemia time, positive surgical margins, or any postoperative complications [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe a significant difference in warm ischemia time in both subgroups, and there was no difference in positive surgical margins or in overall complications. This is in line with Shumate et al’s [26] recently published results of 205 patients undergoing RAPN. In that study, the presence of APF was not associated with warm ischemia time, positive surgical margins, or any postoperative complications [26].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with Shumate et al’s [26] recently published results of 205 patients undergoing RAPN. In that study, the presence of APF was not associated with warm ischemia time, positive surgical margins, or any postoperative complications [26]. Although Khene et al [9] did not find high MAP scores to be an independent risk factor for the development of major postoperative complications, they found the MAP score as continuous variable to be adversely associated with TRFECTA achievement.…”
Section: Discussionsupporting
confidence: 91%
“…Shumate et al, studied the association of APF in perioperative outcomes of 100 patients undergoing RAPN following elimination of the surgical learning curve. This group found that even after elimination of the learning curve, APF was associated with an increased operative time (19). Further studies should be conducted in order to identify additional factors that aid in the prediction of the presence of intraoperative APF in patients undergoing partial nephrectomy (20).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient did not need blood transfusion, and this event did not considerably affect the length of hospital stay since the discharge was on the fifth postoperative day. We had one conversion to laparoscopy due to APF, which is a described limiting factor in robot-assisted renal surgery ( 9 ). Conversions are common, with 1%-10% conversions to laparoscopic adrenalectomy and 1% to open adrenalectomy ( 1 ).…”
Section: Discussionmentioning
confidence: 99%